SINERGI ILMU, SAINS, DAN AGAMA DALAM MENJAWAB TANTANGAN ZAMAN KONTEMPORER: 1. BENTUK UTAMA SINERGI ANTARA SAINS, ILMU, DAN AGAMA, 2. TANTANGAN SINERGI SAINS, ILMU, DAN AGAMA, 3. PERUMUSAN KERANGKA EPISTIMOLOGI INTEGRATIF - Badrut Tamam; Kautsar Eka Wardhana; Yusnia Binti Kholifah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This article explores the synergy between science, knowledge, and religion as an integrative approach to addressing contemporary challenges, including moral issues, environmental crises, and the rapid development of modern technology. The study employs a qualitative descriptive method through a literature review, gathering data from books, journals, and relevant scientific articles. The findings identify four main forms of synergy: conceptual dialogue between theology and science, integration within education, collaboration on socio-environmental issues, and the engagement of scientists with faith communities. These forms of integration demonstrate significant contributions in broadening understanding, strengthening moral legitimacy, and enhancing public participation in strategic issues. Nevertheless, the integration efforts face challenges, both conceptual stemming from epistemological differences and practical, such as limitations in scientific and religious literacy, institutional capacity, and socio-political factors. To address these challenges, this article proposes an integrative epistemological framework that combines empirical-rational methodologies with normative and spiritual dimensions, applicable in education, policy-making, and social practices. In conclusion, the synergy of science, knowledge, and religion is not aimed at blending the two domains but at fostering a productive dialogue that balances scientific rationality with moral-spiritual wisdom, making it highly relevant for building a just, sustainable, and human-centered civilization.